Political risk, project finance, and the participation of development banks in syndicated lending - Hainz, Christa; Kleimeier, Stefanie (Journal of Financial Intermediation, 2012)
How should loan contracts for financing projects in countries with high political risk be designed? We argue that non-recourse project finance loans and the participation of development banks in the loan syndicate help mitigate political risk. We test these arguments by conducting a study with a sample of 4978 loans made to borrowers in 64 countries. Our results show that if political risk is higher, then project finance loans are more likely to be used, and development banks are more likely to participate in the syndicate. We also show that the terms of the loan contract depend not only on the political risk but also on the legal and institutional environment as well.